Perto da justiça, longe do cidadão: a administração judicial das eleições no Brasil (1881-1932) - Souza, Alexandre de Oliveira Bazilio de (2017)
Since the Brazilian Independence, elections have become a central issue in the country’s political debates. In the last decades of the 1800’s, major reforms in that area were put in place, like the Saraiva Law in 1881. Among other changes, the Judiciary was given a major role in the electoral administration, in replacement for lay authorities, mainly the justices of the peace. In order to justify this alteration, the judges were described as impartial, apolitical and, therefore, capable of eliminating or minimize, at the very least, the difficulties surrounding elections. Nonetheless, this new organization of the electoral officials resulted in a decline of electoral turnout, for two main reasons: the wards were centralized in citified areas and the electoral processes became more complex as they adopted the judicial technique. As a result, the Brazilian electorate reduced drastically from about ten percent of the population up to 1880 to just over one percent. After the proclamation of the Republic, despite the drop of income qualifications, the number of balloters remained low, at the same time that additional features of the electoral processes included the insertion of the federal Judiciary – established at the time – into the electoral structure and the issuing of unprecedented electoral writs, such as the habeas corpus. The republican regime also witnessed the return of lay electoral administrators, as a reflex of the controversy associated to the performance of electoral duty by the judges. In 1916, however, the Bueno de Paiva legislation would put the Judicial Power in charge of the elections once again, process consolidated with the passing of the electoral Code in 1932, when the magistrates and its subordinates came to be exclusively responsible for all electoral activities. In this research, I aim at retracing this path between 1881 and 1932, during which the Judiciary was thought and assigned as the main manager of the elections, in order to analyze the impact this had on the development of the country’s citizenship and political culture during the period.